2023
DOI: 10.1002/smll.202303456
|View full text |Cite
|
Sign up to set email alerts
|

Osteophilic and Dual‐Regulated Alendronate‐Gene Lipoplexes for Reversing Bone Loss

Abstract: The pathogenesis of postmenopausal osteoporosis (PMOP) is mainly determined by the adhesion of osteoclasts to the bone matrix and the involvement of various molecules in bone resorption. The dual regulation strategy of the physical barriers of bone matrix and intracellular gene regulation generated by advanced biomaterials is a decent alternative for the treatment of PMOP. Herein, for the first time, it is identified that hsa‐miR‐378i/mmu‐miR‐378a‐3p are closely associated with PMOP. Then, an osteophilic and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The osteophilic and dually regulated isotype replacement antibody @ Aln-Lipo provides a bifunctional strategy for precision therapy of PMOP. 30 Through miRNA-seq sequencing, we screened for key factors by which EC-EXOs regulate the fate differentiation of BMSCs. Our study showed that the expression of miR-3p-975_4191 was significantly greater in EC-EXOs than in BMSCs and HMEC-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The osteophilic and dually regulated isotype replacement antibody @ Aln-Lipo provides a bifunctional strategy for precision therapy of PMOP. 30 Through miRNA-seq sequencing, we screened for key factors by which EC-EXOs regulate the fate differentiation of BMSCs. Our study showed that the expression of miR-3p-975_4191 was significantly greater in EC-EXOs than in BMSCs and HMEC-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…As we already said, the miRNAs are a group of small non-coding RNAs that regulate gene expression at the post-transcriptional level and cellular processes [ 39 , 40 , 41 ]. Notwithstanding most miRNAs are found inside cells, there is a large portion that are release in the body fluids such as blood, urine, saliva, seminal fluid, breast milk and other biological specimens in response to tissue damage, apoptosis and necrosis through active transport into exosomes or bonded to a protein as previously described [ 42 ].…”
Section: Endogenous Mirnas and Bone Metabolismmentioning
confidence: 99%
“…As we already said, the miRNAs are a group of small non-coding RNAs that regulate gene expression at the post-transcriptional level and cellular processes [39][40][41]. Notwithstanding most miRNAs are found inside cells, there is a large portion that are release in the body fluids such as blood, urine, saliva, seminal fluid, breast milk and other biological specimens in response to tissue damage, apoptosis and necrosis through active transport into exosomes or bonded to a protein as previously described [42].…”
Section: Endogenous Mirnas and Bone Metabolismmentioning
confidence: 99%